Conflict and conflict resolution among selected gay and lesbian young adult couples in Metro Manila - Cabrera, Janssen S.; Villanueva, Vanessa R.
ABSTRACT This study explored the areas, intensity, and resolution of conflict among gay and lesbian young adult couples in Metro Manila. Survey questionnaires were administered to each member of 15 lesbian and 13 gay couples (N=56), and face-to-face interview was conducted with one member from each couple (N=28). The results of this study showed that distrust and personal distance were the areas of conflict most frequently encountered and most intensely experienced by both groups. In terms of conflict resolution, both gays and lesbians preferred positive problem solving, but lesbian couples more frequently used deconstructive resolution tactic such as conflict engagement and withdrawal than gays. Filipino behaviors of adapting to conflict through tampo, lambing, and paghihinga were explored.